PERAN NEGARA DALAM PEMBUBARAN PARTAI POLITIK DI INDONESIA - Caroline Tresnoputri; Rasji Rasji (Jurnal Hukum Adigama, 2022)
Indonesia is a democratic country that always tries to guarantee the rights of itscitizens io freedom of association and assembly. The guarantee of this basic rightiisin the state constitution, namely the 1945 Constitution. The right to associate andassemble is a forum for establishing a political party. In the iynamics of the state,it is always related to the dynamics of political parties. These political parties playa very important role in the direction of policies and goals of a country. Theevelopment of a political party can also shake a country, so it is necessary toilimit ithe iestablishment iof ipolitical iparties. The ilimitation iof ithe iright iof iassociationiaims ito iprotect ithe istate iand icitizens. iPolitical iparties iwith idif erent iideologies ifromithe istate iwill ibe idissolved ior ifrozen, ithe imechanism iof iwhich iis ialso iregulated ibyithe istate. iThe idissolution iof ia ipolitical iparty iis ia iform iof istate irestriction ito iensureinational isecurity iand ialso iguarantees ithe irights iof icitizens.